Prognostic Value of the HALP Index, Erythrocyte Sedimentation Rate, and Rheumatoid Factor in Rheumatoid Arthritis: A Laboratory-Based Multivariate Analysis: Prediction model of RA - Xu, Xiaohua; Huang, Xiaohua; Lu, Yongfang; Zeng, Defei (Journal of Medical Biochemistry, 2025)
Background: Biochemical and hematological indices play a critical role in evaluating systemic inflammation and disease activity in rheumatoid arthritis (RA). This study investigated the prognostic value of the hemoglobin–albumin–lymphocyte–platelet (HALP) index, in combination with erythrocyte sedimentation rate (ESR) and rheumatoid factor (RF), for predicting RA disease progression.Methods: A retrospective analysis was performed on 146 RA patients admitted between December 2022 and December 2023. Laboratory variables included HALP index, ESR, RF, C-reactive protein, anti-CCP antibodies, hemoglobin, albumin, lymphocyte and platelet counts, and serum creatinine. Measurements were obtained using standardized automated hematology and biochemical analyzers. Disease activity and radiographic joint damage scores were also assessed. Statistical approaches included correlation analysis, regression analysis, and receiver operating characteristic (ROC) curve evaluation.Results: The HALP index, ESR, and RF were significantly associated with RA disease progression. The HALP index demonstrated a strong correlation with disease activity (r=0.602, P
Keywords: rheumatoid arthritis; HALP index; erythrocyte sedimentation rate; rheumatoid factor; biochemical markers; laboratory medicine